Extended Abstracts of the 2014 International Conference on Solid State Devices and Materials 2014
DOI: 10.7567/ssdm.2014.a-2-5l
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of Read Disturbance Mechanism due to Carrier Trapping in Sub-20nm NAND Flash Memory

Abstract: We observed an increase of V th (charge gain) by read disturbance mechanism at PV1 and ERS states in retention characteristics of sub-20nm NAND Flash main-chip. As a result, we quantitatively modeled read disturbance mechanism by the amount of final ΔV th and deterioration coefficient α which is related to the number of read operation times. It was also observed that those parameters increase with increasing cycling times and have larger value at ERS state than that at PV1 state.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…In a previous research, 27) we modeled read disturbance mechanism observed at PV1 and ERS in sub-20 nm NAND flash memory. In this paper, we show the dependence of read disturbance mechanism on the temperature and analyze the characteristics of read disturbance mechanism more in detail.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous research, 27) we modeled read disturbance mechanism observed at PV1 and ERS in sub-20 nm NAND flash memory. In this paper, we show the dependence of read disturbance mechanism on the temperature and analyze the characteristics of read disturbance mechanism more in detail.…”
Section: Introductionmentioning
confidence: 99%